2014
DOI: 10.1016/s2213-8587(14)70146-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prospective association between individual plasma phospholipid saturated fatty acids and incident type 2 diabetes: the EPIC-InterAct case-cohort study

Abstract: SummaryBackgroundConflicting evidence exists regarding the association between saturated fatty acids (SFAs) and type 2 diabetes. In this longitudinal case-cohort study, we aimed to investigate the prospective associations between objectively measured individual plasma phospholipid SFAs and incident type 2 diabetes in EPIC-InterAct participants.MethodsThe EPIC-InterAct case-cohort study includes 12 403 people with incident type 2 diabetes and a representative subcohort of 16 154 individuals who were selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
396
8
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(467 citation statements)
references
References 30 publications
43
396
8
20
Order By: Relevance
“…Overall, the estimated D6D and SCD1 activities were strongly associated and the estimated D5D activity was inversely associated with the development of type 2 diabetes, as previously reported [14,27]. We also showed that the most abundant SFAs were associated with an elevated risk of diabetes, in agreement with two recent studies showing associations with type 2 diabetes [17,28]. Total SFAs were associated with impaired insulin sensitivity and insulin secretion in our study, offering a mechanistic explanation for how SFAs may impair glucose tolerance and lead to type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the estimated D6D and SCD1 activities were strongly associated and the estimated D5D activity was inversely associated with the development of type 2 diabetes, as previously reported [14,27]. We also showed that the most abundant SFAs were associated with an elevated risk of diabetes, in agreement with two recent studies showing associations with type 2 diabetes [17,28]. Total SFAs were associated with impaired insulin sensitivity and insulin secretion in our study, offering a mechanistic explanation for how SFAs may impair glucose tolerance and lead to type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Odd chain fatty acids (15:0 and 17:0) were not associated with impaired insulin sensitivity or insulin secretion. Evidence in earlier studies also suggests an inverse association of pentadecanoic acid 15:0 and margaric acid 17:0 with the risk of type 2 diabetes [15,28,32]. Odd chain fatty acids are found in milk fat and fish [33][34][35][36].…”
Section: Discussionmentioning
confidence: 90%
“…Rate of stricture in RFA procedure 9% - [19] Rate of perforation in RFA procedure 0.1% Clinical expert opinion -Mortality from esophagectomy 4.3% - [16] All-cause mortality Dependent on starting age and cycle in the model - [33] EMR: Endoscopic mucosal resection; HGD: High-grade dysplasia;…”
Section: Safety Inputsmentioning
confidence: 99%
“…The mechanism of the inhibitory role of C15:0 on proliferation of cancerous cells is similar to that of CLA. The intake of odd-chain saturated fatty acids is also related to a reduced incidence of type II diabetes in humans (Forouhi et al, 2014). Thus, further studies are needed to evaluate the effects of crude glycerin on the synthesis and biohydrogenation of fatty acids and rumen bacteria involved in this process, in order to obtain meat with healthier fatty acid profile for human consumption.…”
Section: Resultsmentioning
confidence: 99%